Teaching and research in mid-career management education: Function and fusion. (March 2016) - Quinn, Bríd C
The apparent disconnect between teaching and research has implications for both curricular content and pedagogic practice and has particular salience in the field of mid-career education. To overcome this disconnect, faculty endeavour to integrate teaching and research. Pressure to do so stems from many sources. Benchmarks of professional excellence as well as the scholarship of teaching and learning champion such synergy. Institutions advocate teaching that is informed by research and research that is relevant to students. This article explores the conceptual and instrumental arguments for linking research and teaching. It discusses the benefits of such linkages and the challenges in effecting them. The exploration provides a conceptual base for other contributions in the volume which demonstrate specific research–teaching synergies in the Public Administration/Public Management classroom.